(untitled) (Journal of Parents and Teachers, 2014)
The school has a very important role since it transmits culture and, therefore, forms citizens capable of living in society; it is the teacher who will take care of this. This article talks about the teacher’s job and the importance of knowing how to transmit the values of society to the students. The article explains that the teacher must be seen as a mediator, facilitator, intermediary, and guide.